TINGGALAN ARKEOLOGI NON EKSKAVASI DI SITUS BENTENG PUTRI HIJAU - Ponirin, Ponirin; Mendrofa, Dena Lovita (Universitas Negeri Medan, 2018)
This study aims to find out the archaeological findings of non-excavations at the Putri Hijau Fortress site, the views of the people and archaeologists on the findings of non-excavation archeology objects, and to find out the significance of these findings for the world of archeology. File collection was carried out through field research directly at Benteng Putri Hijau Site, by conducting interviews with communities around the site and community leaders and research teams engaged in archeology and history who also conducted research on the site. Besides that the author also uses literature research, by examining books or documents that are relevant to the topic under study. The results showed that the Green Princess Fortress Site once stood an empire whose names began to appear around the 13th century. Many famous explorers and writers both foreign writers and domestic writers wrote the name of this kingdom in Cheng Ho, Tom Pires, Ferdinan Mendez Pinto, Jhon Anderson, Tengku Lukman Sinar, Tengku Lah Husni. All of these writers wrote about how Aru in his heyday had so much power that the name of this kingdom was included in one of the most famous vows, namely Palapa Oath by Patih Gajah Mada from Maja Bahit. This kingdom disappeared due to its defeat from the kingdom of Aceh around the end of the 16th century. That made this kingdom collapse and left a silent witness of a fortress called the Putri Hijau Fortress, where the name was taken from one of the famous figures who are well known and legendary in the community around and the people of Sumatra are Putri Hijau. Several other relics were also found, such as gold coins, ceramics, bullets, rocks and so on ... Attention to the Benteng Putri Hijau site was increased due to efforts to damage housing development around the beginning of 2008. So archeology and excavation activities were held rescue in October 2008 and May 2009 by the Banda Aceh Conservation Agency (BPCB), Medan Archeology Center, North Sumatra Museum, Deliserdang Cultural and Tourism Service, UNIMED Pussis, USU and other related parties. The main objective in this activity was an effort to save the Green Princess Fortress site which had been damaged. This research is rated to be able to help provide information and collect archeology remains that are still on the site of the green princess fortress, including collecting data and remains of non-excavation archeological objects at the Putri Hijau Fortress site which was also accidentally discovered by local residents.